Tarzan and the Jewels of Opar - Burroughs, Edgar Rice, 1875-1950 (Salt Lake City, UT : Project Gutenberg, 1993)
"Tarzan and the Jewels of Opar" by Edgar Rice Burroughs is a novel first published in 1916. Tarzan returns to the lost city of Opar to recover gold from its hidden treasure stockpile after suffering financial losses. But danger follows$1 (Ba treacherous Belgian officer tracks him, an earthquake leaves him without memory, and the beautiful high priestess La seeks vengeance after he rejects her love again. Meanwhile, Jane has been kidnapped, and an amnesiac Tarzan must navigate intrigue and betrayal while unknowingly carrying Opar's sacred sacrificial knife. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Tarzan_and_the_Jewels_of_Opar
Release date is 1993-12-01
Judith Boss
Keywords: Tarzan (Fictitious character) -- Fiction; Fantasy fiction; Adventure stories